Сценарий работы инженера-технолога в среде интеллектуальной экспертной системы - Кравцов А. В. Анатолий Васильевич; Новиков А. А.; Коваль П. И.; Навоенко С. В. (Томск, 1999)
Деп. в ВИНИТИ 10.02.99, № 439-В99